1991
DOI: 10.1071/pp9910603
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low O2 Concentration and Azide on Hydraulic Conductivity and Osmotic Volume of the Cortical Cells of Wheat Roots

Abstract: The short-term effects of O2 deficiency and sodium azide (NaN3) on the hydraulic conductivity of cortical cells in wheat roots was studied using the pressure probe. Hydraulic conductivities were obtained by measuring either turgor relaxation, or volume relaxation under pressure clamp. Both low O2 concentration and NaN3 increased the half times of pressure and volume relaxations. The increases in T½ were found to be due to a decrease in the hydraulic conductivity (Lp) of the cells. The mean values of Lp from pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
2
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 32 publications
4
68
2
1
Order By: Relevance
“…We assume changes in these gases in the flood water (Table I) interfere with the normal increase and decrease of L, during the 1st d of flooding and induce a temporary depression of conductivity across membranes (Zhang and Tyerman, 1991). Such effects may be mediated by conformational changes in the water channel proteins (aquaporins).…”
Section: Does Soil Flooding Change F?mentioning
confidence: 99%
“…We assume changes in these gases in the flood water (Table I) interfere with the normal increase and decrease of L, during the 1st d of flooding and induce a temporary depression of conductivity across membranes (Zhang and Tyerman, 1991). Such effects may be mediated by conformational changes in the water channel proteins (aquaporins).…”
Section: Does Soil Flooding Change F?mentioning
confidence: 99%
“…Perhaps some improvement in the determination of V may be obtained by the method of Malone and Tomos (19901, and this will hopefully improve the accuracy of qnst estimates. However, Zhang and Tyerman (1991) found that for cortical cells of wheat roots, the calculated cell volumes were about twice the optically determined volumes, unless the roots were subjected to anoxia or azide. Cosgrove and Steudle (1981) were not able to determine the pressure dependence of einst for cortical cells of pea.…”
Section: Discussionmentioning
confidence: 99%
“…Routine correction for dynamic (K h ) effects required measurement of either tip pneumatic conductance (K p ) or tip size (Fig. 2C), but because the data for K p was routinely available as part of microcapillary manufacturing (Wada et al, 2011) , very similar to the hydraulic resistance of tips of a similar size reported by Zhang and Tyerman (1991). From Equation 2 (P cell 2 P oil = a/r m + dV/ dt 3 1/K h ), the differences between measured P oil and P cell due to K h were generally less than 0.0001 MPa; hence, for the tips and cells used in this study, the effects of K h and surface tension were very small, but the magnitude of both of these effects will increase if smaller tips are used.…”
Section: Comparison Of Acpp and Cell Pressure Probementioning
confidence: 99%
“…In the PC method, first developed by Wendler and Zimmermann (1982), V o (and, given reasonable assumptions about cell geometry, A) is estimated without the need for optical measurements, and L p can be measured without the need to determine dP/dV or «. However, this method is technically more demanding because it requires precise P control as well as a continuous record of the volume flow of water across the cell membrane (as measured by changes in the position of the cell solution/oil meniscus within the glass capillary over time) and has rarely been used Zimmermann, 1982, 1985;Cosgrove et al, 1987;Moore and Cosgrove, 1991;Zhang and Tyerman, 1991;Murphy and Smith, 1998). Since volume (V) is continuously changing over time, this approach may also be influenced by the hydraulic conductance of the capillary tip (K h ) used to make the measurements as well as surface tension effects due to the progressive changes in capillary diameter with meniscus position, and these influences have not been quantitatively addressed.…”
mentioning
confidence: 99%